Applicable Law in the Intercountry Succession Cases - Bronušienė, Simona (Teisė, 2018)
From the 17 August 2015 in the EU member states, except Denmark, UK and Ireland, there is applied regulation No 650/2012, which establishes legal rules on jurisdiction, applicable law, recognition and enforcement of decisions and acceptance and enforcement of authentic instruments and on the creation of a European Certificate of Succession in the matters of intercountry succession. As the substantive succession law of the EU member states still holds a lot of differences, in the cases of intercocuntry succession it becomes very important to determine applicable law not only when the succession is already opened but also before it, when the testator is still alive and plans its estate post mortem. In the article there are overviewed the legal rules on applicable law before the application of regulation No 650/2012 and the changes brought by regulation, such as the unity of the succession, common connecting factor – last habitual residence of de cujus and possibility for testator to choose applicable law (profesio iuris). Also in the article there is analized the content of the applicable law, its coherance with other related matters and the legal instruments regulating them and also the newest practice of CJEU. The purpose of this article is to reveal the changes in determining the applicable law in intercountry succession cases and its benefits and challanges for interested parties.
Keywords: none